2019
DOI: 10.1051/matecconf/201926804014
|View full text |Cite
|
Sign up to set email alerts
|

Production of composite membrane from waste Kappa-Carrageenan and Tilapia (Oreochromis niloticus) fishbone

Abstract: Kappa-Carrageenan has been widely used as a gelling agent and stabilizer in the food industry. This research is an application of Kappa Carrageenan as polymer membrane with the combination of Hydroxyl Apatite obtained from the fishbone. Different weight percentages of K-Carrageenan and Fishbone were mixed to make a filtering media with the use of Glutaraldehyde as a crosslinking agent. Before the crosslinking, K carrageenan were pretreated with monochloroacetic acid, ethanol and sodium hydroxide to become an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…(2018) also showed that HAp biochar can be produced from Tilapia bone using carbonization at 550°C with high adsorptive power against heavy metals and dyes in water and wastewater. Olay et al . (2019) revealed the presence of a large amount of hydroxyl group in HAp derived from fish contributing to a significant increase of the active adsorbing sites for the heavy metals like lead, arsenic, copper, cadmium, and mercury with adsorption capability of 162.4 mg/g for copper and 128.7 mg/g for cadmium.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) also showed that HAp biochar can be produced from Tilapia bone using carbonization at 550°C with high adsorptive power against heavy metals and dyes in water and wastewater. Olay et al . (2019) revealed the presence of a large amount of hydroxyl group in HAp derived from fish contributing to a significant increase of the active adsorbing sites for the heavy metals like lead, arsenic, copper, cadmium, and mercury with adsorption capability of 162.4 mg/g for copper and 128.7 mg/g for cadmium.…”
Section: Discussionmentioning
confidence: 99%